Synthesis, characterization and acute toxicity of new Schiff base derived from L-arginine and vanillin - Al-Masoudi, Wasfi Aboud; Al-Diwan, Mohammed Ali; Khayoon, Orass Saad (European Journal of Chemistry, 2016)
Condensation of L-arginine with 4-hydroxy-3-methoxy benzaldehyde (vanillin) yielded a novel Schiff base derivative of arginine in good yield. This new Schiff base was characterized by elemental analysis, IR and 1H NMR spectroscopy. The toxicity of the compound was also assayed via the determination of their LD50 value by using Dixon method. Studied compound was found to have an LD50 of 718.6 mg/kg of body weight.